DIGITAL TRANSFORMATION OF CUSTOMS ADMINISTRATION AS A DRIVER OF MODERNIZATION OF THE STATE CUSTOMS SECTOR (INNOVATIVE ECONOMY, 2026)
Sydorovych O.Yu., Smaliuk A.M. Digital Transformation of Customs Administration as a Driver of Modernization of the State Customs SectorPurpose. The aim of this article is to provide a comprehensive examination of the current state of digital transformation of customs administration in Ukraine, identification of key challenges, constraints and priority directions for the digital transformation of the state’s customs system in the context of contemporary security challenges.Methodology of research. A combination of general scientific and specialised methods of scientific inquiry were used in the research process, in particular, the methods of induction and deduction were applied at the stage of collecting, systematizing, and generalizing information in order to identify trends in the development of the digital transformation of customs administration. The methods of analysis and synthesis were used to assess the current state of implementation of information products in the activities of the customs authorities of Ukraine, as well as to formulate generalized conclusions regarding the effectiveness of digital transformations. Findings. The theoretical and methodological foundations of the digital transformation of customs administration have been examined, and current trends in the implementation of information and communication systems within the activities of the customs authorities of Ukraine have been analysed, in particular the development of electronic declaration, transit control systems (NCTS), customs risk management, electronic guarantees, and integrated digital platforms for interaction with foreign economic activity operators. It has been established that the digitalization of customs administration significantly increases the efficiency of customs control, ensures the acceleration and simplification of customs procedures, reduces the administrative burden on business, and enhances the transparency of customs operations. It has been determined that the further development of the digital transformation of the customs sector is associated with deeper integration of national IT systems into the European digital customs space, harmonization with the requirements of the EU Customs Data Model and MASP-C, as well as the improvement of the architecture of interaction between customs information systems. Promising directions include the development of intelligent analytical tools, the expansion of automated control systems, and the strengthening of cybersecurity within the customs IT infrastructure.Originality. For the first time, it has been substantiated that the digital transformation of customs administration is a holistic, multidimensional process of institutional, organizational, and technological modernization of the customs sphere, which, unlike existing approaches, is based on the integrated implementation of the principles of systemacity, interoperability, risk-oriented management, cybersecurity, and harmonization with international standards, thereby enabling the formation of an adaptive model of customs administration compatible with the European digital environment. The scientific substantiation of the role of digital transformation of the customs sector as a key driver of modernization of the state's customs system has been improved, which, unlike traditional approaches, takes into account the complex impact of European integration processes, security challenges, and the need for synchronization with European digital customs standards.The identification of key areas for the implementation of digital technologies in the customs sector has been further developed, in particular the development of electronic declaration and transit control systems (NCTS), the use of risk-based analytical tools, the digitalization of customs clearance procedures, and the integration of the national customs IT architecture into the EU Customs Data Model and MASP-C standards, which allows for increased efficiency of customs control and transparency of customs procedures.The position that deepening the digital transformation of customs administration creates the prerequisites for creating a modern, effective and institutionally capable customs system of Ukraine, compatible with the EU digital infrastructure, was further developed.Practical value. The conclusions and proposals substantiated within the study can be used in the formation of strategic directions for the development of digital tools in the customs sector of Ukraine, contributing to increased efficiency of the customs system, reduction of the shadow economy, and strengthening of the fiscal stability of the state under conditions of digital transformation and global economic challenges.Key words: customs administration, digital technologies, digital transformation, digitalization, customs control, customs sector, customs modernization, NCTS, AEO.
Keywords: customs administration; digital technologies; digital transformation; digitalization; customs control; customs sector; customs modernization; NCTS; AEO